2023
DOI: 10.1155/2023/4376579
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and Mineralization Activity of Calcium Silicate-Based Root Canal Sealers Compared to Conventional Resin-Based Sealer in Human Gingival Fibroblast Cells

Abstract: Background. Root canal obturation is performed by gutta-percha cones and sealer. Therefore, these materials, specially sealers, must be biocompatible. This study investigated the cytotoxicity and mineralization activity of two calcium silicate-based sealers (Endoseal MTA and Ceraseal) and an epoxy resin-based sealer (AH26). Materials and Methods. In this experiment, the cytotoxicity of Endoseal MTA, Ceraseal, and AH26 on human gingival fibroblast cells was examined using Methyl-Thiazol-Tetrazolium assay at tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…On the other hand, the favourable biocompatibility exhibited by the tested CSSs is consistent with previous evidence on other CSSs [ 56 58 ]. Specifically, AHPbcs also showed a favourable cytocompatibility on human periodontal ligament fibroblasts (hPDLFs) using an MTT [ 25 ] and an XTT assay [ 27 ] on previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, the favourable biocompatibility exhibited by the tested CSSs is consistent with previous evidence on other CSSs [ 56 58 ]. Specifically, AHPbcs also showed a favourable cytocompatibility on human periodontal ligament fibroblasts (hPDLFs) using an MTT [ 25 ] and an XTT assay [ 27 ] on previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…Numerous studies suggested that CSBS sealers may present lower cytotoxic potential contrasted to other types of root canal sealers 25 , 44 48 . In the case of bioceramic sealants, the cytotoxic effect may be related to the release of substances during the setting and subsequent dissolution of the material (calcium ions) 40 , the addition of radiopacifiers or thickening agents 49 , the content of oxides, mainly barium oxide 50 , and the formation of hydroxyapatite 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Stem cells from the elderly, similar to cells from the young, exhibit a reaction to these signals [ 87 , 89 ]. In contrast, a study by Tiantian Wu et al [ 56 ] demonstrated that the use of calcium silicate cement significantly influenced cell viability, the high alkalinity of the calcium silicate-based sealer media can up-regulate alkaline phosphatase activity and enhance mineralization [ 56 , [90] , [91] , [92] , [93] , [94] ].…”
Section: Discussionmentioning
confidence: 99%